Stanozolol and Danazol Have Different Effects on Hematopoiesis in the Murine Model of Immune-Mediated Bone Marrow Failure - Li, Hongmin; Long, Zhangbiao; Wang, Tao; Han, Bing (Frontiers in Medicine, 2021)
Background: Stanozolol and danazol are widely used in the treatment of aplastic anemia; however, their mechanisms of action are unclear. Methods: Bone marrow mononuclear cells from 10 patients newly diagnosed with aplastic anemia and 10 healthy volunteers were collected and cultured together with stanozolol, danazol, or blank control separately for marrow colony assays. K562 cell lines that had been incubated with stanozolol, danazol, or blank control were tested for erythroid or megakaryocytic differentiation. Meanwhile, CB6F1/Crl mice were injected with 1 × 106 C57BL/6 donor-originated lymphocytes after irradiation with 5 Gy total body irradiation to establish a model for immune-mediated bone marrow failure (aplastic anemia mouse model). Mice with aplastic anemia were treated with cyclosporin A monotherapy, cyclosporin A in combination with stanozolol, and cyclosporin A in combination with danazol for 30 days. Peripheral blood cell counts once a week and bone marrow colony assays at the end of 1 month were performed. The proportion of T cell subsets, level of inflammatory factors, erythropoietin, and thrombopoietin were detected before and after treatment. The levels of erythropoietin receptors on bone marrow mononuclear cells after treatment were tested using western blotting. Results: In the ex vivo experiments, the number of burst-forming units-erythroid; colony-forming units-granulocyte and macrophage; and colony-forming units-granulocyte, erythrocyte, monocyte, and megakaryocyte in the patients with aplastic anemia were significantly lower than that in the normal controls (P < 0.05). However, the number of colonies and mean fluorescence intensity of CD235a or CD41 expression in the harvested cultured cells were not significantly different among the different treatment groups in the patients with aplastic anemia, normal controls, and K562 cell lines. These results show that stanozolol and danazol produce no direct hematopoiesis-stimulating effects on progenitor cells. In the in vivo experiment, the mice with aplastic anemia treated with cyclosporin A and danazol exhibited the most rapid recovery of platelet; the platelet count returned to normal levels after 3 weeks of treatment, which was at least 1 week earlier than in the other groups. In contrast, mice treated with cyclosporin A and stanozolol exhibited the highest hemoglobin level at the end of treatment (P < 0.05). Bone marrow colony assays at 30 days showed that the number of burst-forming units-erythroid was the highest in mice treated with cyclosporin A and stanozolol, while the number of colony-forming units-granulocyte and macrophage was the highest in those treated with cyclosporin A and danazol. Compared to cyclosporin A monotherapy, additional stanozolol and danazol can both increase the level of regulatory T cells and upregulate interleukin-10, inhibiting the expression of tumor necrosis factor-α (P < 0.05). However, IL-2 was more effectively reduced by danazol than by stanozolol (P < 0.05). The cyclosporin A- and stanozolol-treated mice showed higher serum erythropoietin (corrected by hemoglobin level) and higher erythropoietin receptor levels in bone marrow mononuclear cells than the other groups (P < 0.05). Conclusions: Neither stanozolol nor danazol directly stimulated hematopoiesis in vitro. However, in vivo, stanozolol may exhibit an advantage in improving erythropoiesis, while danazol may induce stronger effects on platelets. Both danazol and stanozolol exhibited immunosuppressive roles. Stanozolol could enhance the secretion of erythropoietin and expression of erythropoietin receptor in bone marrow mononuclear cells.